A Decision Support System For The Selection Of The Best Employees At CV. Adiguna By Applying The Preferences Selection Index Method - Putra, Repal Kesatria; Yupianti, Yupianti; Beti, Ila Yati; Lianda, Deri (LPPJPHKI Universitas Dehasen Bengkulu, 2023)
Technological Developments at this time, competition in the business world is getting tougher, to support this, companies must also improve their quality. On CV. Adiguna to increase the resources of his employees in improving the quality of his company is of course supported and influenced by the performance of employees who are competent in their field. Where in CV. Adiguna of Bengkulu City in giving awards to the best employees every year so far it is still done manually, this can certainly increase the enthusiasm of employees at work and always run a business by fulfilling several criteria set by CV Adiguna of Bengkulu City. Therefore to provide an objective assessment of employee performance, a Decision Support System is needed to select the best employees and provide rewards to employees, then to support the above, it is necessary to implement several Decision Support Systems at CV Adiguna of Bengkulu City based on the criteria that have been determined by the management of CV Adiguna of Bengkulu City. Decision support system for selecting the best employees at CV Adiguna of Bengkulu City by applying the Preferences Selection Index method is a desktop-based application that has implemented the Preferences Selection Index (PSI) method. This application can be used to assist in the process of selecting the best employees on CV Adiguna of Bengkulu City uses 5 predetermined criteria, then the assessment of these 5 criteria is processed using the Preferences Selection Index (PSI) method to produce a ranking that will be used to determine the best employee. Based on the results of the tests that have been carried out, it can be concluded that the decision support system for selecting the best employees at CV Adiguna of Bengkulu City by applying the Preferences Selection Index method is able to run well and can overcome data input errors besides that calculations are done manually with those carried out by the application producing the same output.